The Effects of Overeducation on Productivity in Germany - The Firms' Viewpoint - Felix Büchel (Institute for the Study of Labor (IZA), 2000)
Several firm-related aspects of employee productivity are analyzed using GSOEP data. The basic premise is that, as a consequence of frustration, overeducated employees are less productive than their correctly allocated colleagues. However, the results obtained in the present study contradict the few available empirical findings, all of which are based on data from the United States. When comparing employees working in jobs with similar levels of requirements (the sole approach which seems to be useful), overqualified employees are found to be healthier, more strongly work- and career-minded, more likely to participate in on-the-job training, and to have longer periods of tenure with the same firm than their correctly allocated colleagues. No significant differences could be determined with respect to job satisfaction. These findings are consistent with the established fact that overeducated workers receive wage premiums for their surplus schooling. The overall results make the hiring of overqualified applicants understandable, and could explain the employers? motivation to accept persistent overeducation in the labor force.
Keywords: J28; J63; J21; J24; 330; Overeducation; productivity; labor demand; job satisfaction; work- and careerorientation; health; on-the-job training; firm tenure; Qualifikation; Erwerbsverlauf; Arbeitsproduktivität; Lohnstruktur; Deutschland; Überqualifizierung